The Implementation of Internal and External Quality Assurance Systems at the Private Islamic Higher Education: (A Case Study at STAI Al Badar Cipulus Purwakarta) - Herniawati, Ani; Miftahudin, Ujang; Jamil, Zam zam Lukmanul; Hidayat, Yusuf; Ruswandi, Uus (CV. Tripe Konsultan, 2024)
Quality assurance at higher education becomes main priority, including at private Islamic higher education (PTKIS). This study analyzes the implementation of SPMI and SPME and identifies the obstacles and strategies taken to optimize the implementation of SPMI and SMPE at STAI Al Badar Cipulus Purwakarta. This study employs qualitative approach under a case study, at which the data were collecyed through interview, observation, and document analysis. The findings of the study show that the implementation of SPMI and SPME at STAI Al Badar Cipulus Purwakarta refers to planning, implementing, monitoring, evaluating, and improving the quality of education which is carried out by involving the entire academic community, including institustion leaders, lecturers, and quality management staff. In addition, the obstacles faced by STAI Al Badar in implementing SPMI and SPME consist of internal and external obstacles. Meanwhile, the strategies taken to optimize the implementation of SPMI and SMPE cover: (a) human resource training, (b) technology use training, and (c) strengthening strategic partnerships.